2014
DOI: 10.2139/ssrn.2529984
|View full text |Cite
|
Sign up to set email alerts
|

Bowling Alone or Bowling at All? The Effect of Unemployment on Social Participation

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 39 publications
2
27
0
1
Order By: Relevance
“…It has been found that the unemployed engage in social activities less often (see e.g. Kunze and Suppa, 2017) and have less social support from close relations and authority figures compared to employed individuals (see e.g. Jackson, 1999).…”
Section: The Consequences Of Job Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that the unemployed engage in social activities less often (see e.g. Kunze and Suppa, 2017) and have less social support from close relations and authority figures compared to employed individuals (see e.g. Jackson, 1999).…”
Section: The Consequences Of Job Lossmentioning
confidence: 99%
“…Clark andOswald, 1994 andKassenboehmer andHaisken-DeNew, 2009) and between unemployment and social ties (see e.g. Eliason, 2012 andKunze andSuppa, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Arulampalam et al 2001) and the loss of non-monetary welfare (e.g. reductions of social participation and identity utility, see Kunze andSuppa 2014, Hetschko et al 2014). As a result, we argue that increasing risk of job loss will cause workers to avoid other controllable risks more often as decreasing absolute risk aversion (DARA) characterises their utility function.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the economic importance of the norm effect turns out to be weak, our findings put some caution on the hysteresis argument. Rather, alternative explanations, e.g., the access to social networks, may be important (Kunze & Suppa, 2014). Hence, an adequate policy response to unemployment should consist of a prompt policy reaction with a particular focus on supporting the unemployed in retaining their social networks.…”
Section: Discussionmentioning
confidence: 99%